Translation and validation of household food insecurity access scale (HFIAS) and factors associated with food insecurity among households with children aged five to six years old in Tumpat, Kelantan - Maarof, Mohd Irwan (2018)
Introduction: Food security was defined as, when all people, at all times, has physical and economic access to sufficient, safe and nutritious food to meet their dietary needs and food preference for an active and healthy life (World Food Summit, 1996). The concept of food security encompasses of four dimensions namely access, availability, utilization and stability. Methods: The objective of first phase of this study was to translate the Food Insecurity Access Scale (HFIAS) into Malay and to determine its validity and reliability. The second phase was to determine the household food insecurity and its related factors among children aged five to six years in Tumpat, Kelantan. Phase one involved 60 mothers or female caregivers for children aged five to six years in Bachok, Kelantan. The second phase was a cross sectional study conducted at 45 TABIKA in Tumpat district. It has involved 370 mothers or female guards to children aged five to six years old. All participants were randomly selected. HFIAS has been used to measure the level of household food security (access) and the translated and validated Radimer / Cornell and Hunger scale has been used to measure the level of household food security (availability). The body mass index (BMI) was used to determine the nutritional status of children. The validity of HFIAS constructs translated into Malay has been tested using the method of exploratory analysis. The reliability of the translated questionnaire was expressed as Cronbach alpha. The factors that associated to the underlying status of food security and child malnutrition have been identified through multiple logistic regression analysis. Results: Two major components have been identified from exploratory analysis factors which are quality component and insufficiency component with good reliability index (Cronbach's α = 0.83). A total of 36 (9.7%) households were identified as households with mild food insecurity, 64 (17.3%) moderate and 47 (12.7%) severe household food insecurity. The level of education of mothers who did not receive any formal education or only primary education [Adj: 8.77 (95% CI: 1.80, 42.69; p-value = 0.007)], total monthly income per capita less than RM130 [AdjOR: 4.71 (95% CI : 2.19, 10.08; p-value <0.001)] and the absence of monetary savings [AdjOR: 3.97 (95% CI: 2.45, 6.43; p-value <0.001)] has been identified as associated factors to the household food insecurity (access) . Mothers who have no formal education or just primary education [AdjOR: 3.97 (95% CI: 1.04, 15.16; p-value = 0.043)], mothers who have secondary education [AdjOR: 4.28 (95% CI: 1.55, 11.79; p-value = 0.005)], total monthly income per capita of less than RM130 [AdjOR: 3.10 (95% CI: 1.50, 6.41; p-value 0.002)], total monthly income per capita between RM130 and RM210 [AdjOR: 1.83 (95% CI: 1.10, 3.06; p-value 0.021)] and the absence of monetary savings [AdjOR: 2.71 (95% CI: 1.74, 4.22; p-value <0.001)] has also been identified as associated factors to household food insecurity (availability) Families receiving financial assistance [AdjOR: 1.63 (95% CI: 1.05, 2.52; p-value = 0.028)], absence of land ownership [AdjOR: 1.99 (95% CI: 1.14, 3.50;p-value = 0.016)] and girls [AdjOR: 1.68 (95% CI: 1.10, 2.56; p-value 0.017)] were found to be associated with malnutrition status of children. Conclusion: The HFIAS that has been translated into Malay can be used to measure the access components of household food insecurity in local setting. Household food insecurity need to be handled by taking into account the level of maternal education and monthly income per capita that will enable families to have monetary savings in order to improve household food security that will address the problem of pre-school children's malnutrition.